2013
DOI: 10.4097/kjae.2013.64.4.301
|View full text |Cite
|
Sign up to set email alerts
|

Antihyperalgesic effects of dexmedetomidine on high-dose remifentanil-induced hyperalgesia

Abstract: BackgroundDexmedetomidine is a highly selective α2 adrenergic agonist that has been shown to decrease the intensity of opioid-induced hyperalgesia (OIH). We aimed to investigate the antihyperalgesic effects of dexmedetomidine on high-dose remifentanil-induced hyperalgesia.MethodsNinety American Society of Anesthesiologists physical status I-II patients undergoing laparoscopically assisted vaginal hysterectomy (LAVH) were randomly assigned to one of the following three groups, each of which received either dexm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
64
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(75 citation statements)
references
References 29 publications
10
64
1
Order By: Relevance
“…Our finding that chronic pain was especially observed in patients receiving a higher dose of remifentanil further supports this. A dose‐dependent relationship is also in line with previous reports …”
Section: Discussionsupporting
confidence: 93%
“…Our finding that chronic pain was especially observed in patients receiving a higher dose of remifentanil further supports this. A dose‐dependent relationship is also in line with previous reports …”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, VAS scores were significantly lower in groups with either high or low dose of dexmedetomidine compared with the groups receiving placebo. Our data correspond with other supporting evidence indicated that dexmedetomidine infusion efficiently alleviated RIH symptoms (35,36). …”
Section: Discussionsupporting
confidence: 92%
“…This result was consistent with other animal studies that suggested combination of α2 adrenergic receptor agonist with an opioid can increase analgesic potency to some extent (33,34). Moreover, by effectively suppressing glial cell proliferation and activate the adjacent nerve cells involved in peripheral and central sensitization, dexmedetomidine has been shown effectively decreasing hyperalgesia by increasing acetylcholine levels in the spinal cord (35). Several clinical trials and case reports have confirmed that dexmedetomidine as an α2 adrenergic agonist has the potential to synergize with opioids (4,15,35).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…3,9,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] Other control agents included fentanyl, [33][34][35][36] remifentanyl, 37,38 meperidine, 15 midazolam, [39][40][41] propofol, 43,44 ketamine, 45,46 tramadol, 24,47 clonidine, 42 propacetamol, 48 and buprenorphine 49 ( 8 were reported in the 39 included trials, and all studies reported every endpoint mentioned in the Methods section (reporting bias). 8 however, some bias 8 may exist in of the two trials, 27,32 as the length of surgery was not clear.…”
Section: Study Characteristicmentioning
confidence: 99%